The Impact of the COVID-19 Pandemic on the Proliferation of the Chalet Phenomenon and Changes in Land Use in the Southern Shouneh Region - Alnajjar , Shadi; Makhamreh, Zeyad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to analyze the impact of the COVID-19 pandemic on the changes in land use patterns and the proliferation of chalets in the Southern Shouneh region. Methods: The study employs an analytical approach, using satellite imagery of the Sentinel type to analyze and track changes in land use patterns between 2017 and 2021. Three specific questionnaires were designed and distributed to chalet visitors, chalet owners, and local community residents to gather their opinions on this phenomenon. Results: The results show that the predominant land use in the region is agricultural, followed by urban use in residential areas. There is a clear increase of chalet farms in the Southern Shouneh region, with 70% of these chalets being less than three years old, indicating an increase in the spread of recreational swimming pools in residential areas. Al-Joufeh area attracts the most chalet visitors and farm owners, accounting for 35% of chalet visitors, followed by Al-Karama and Al-Shouneh Al-Jadida at 31%. The majority of chalet visitors are university students, constituting up to 66%, using chalets as a getaway during holidays. The average monthly income of 65% of chalet visitors and farm owners is less than 400 Jordanian dinars, indicating a middle-income status. Conclusions: The study indicates that the major reason for the proliferation of chalets is the occurrence of the COVID-19 pandemic. These chalets serve as unrestricted social outlets with affordable costs, particularly for middle-income individuals and students. The study recommends further investigation of the social and economic impacts of this phenomenon and emphasizes the importance of engaging with the local community and municipality to regulate the establishment of chalets.